PEMANFAATAN EKSTRAK KUNYIT DAN BAWANG PUTIH SEBAGAI NUTRISI TAMBAHAN ALAMI PADA PAKAN DAN APLIKASINYA TERHADAP BENIH IKAN LELE DUMBO (Clarias gariepinus) - BOBY DANI DARMAWAN (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2008)
Nowadays, the chemical ingredients of several additional foods had known as carcinogenic materials. To avoid that, some kind of natural materials are used to be an alternative which it safe and had a lot of important function because of their bioactive essences. Some of them are curcuma ginger and union. This research is done to prove the advantages of using natural additional nutrition from curcuma ginger and union’s essences for African catfish growth performance. The survival and growth performance of African catfish (Clarias gariepinus) fingerlings fed with natural additional nutrition from curcuma ginger and union’s essences raising better than normally nursery. After 45 days rearing period, the percentage fingerling survival for the treatment is 98.33% better than control that only 86.67%. Fingerlings with treatment had the greatest average daily growth, mean body weight, and final average length and was significantly different (p<0.05) from control. Beside of that, the treatment with additional nutrition has undirectly effect to water balance system. This treatment could stabilize the water pH on rearing aquarium.